Characterization and Cracking Activity of Zeolite Prepared from Local Kaolin - A.K. Mohammed, Abdul Halim; Karim, Samar; M. Rahman, Ameel (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
The synthesis of zeolite NaX from locally available kaolin has been studied. The operating conditions for zeolite NaX production from kaolin with good crystallinity were as follows; a gel formation step of metakaolin in alkaline medium in presence of additional silica to crystallize the zeolite was achieved at 60 oC for 1 hr,and with stirring. In ageing step of the reactants at room temperature for 5 days and crystallization step at 87±2 oC for 24 hr. The catalytic activity of catalyst prepared from local kaolin was studied by using cumene cracking as a model for catalytic cracking and compared with standard HY zeolite and HX zeolite catalysts. The activity test was carried out in a laboratory continuous flow unit with fixed bed reactor at duration time in the range 10-240 minutes, temperature 823 K, and LHSV 1 h-1. The prepared and the standard catalysts were characterized by atomic absorption, X-Ray Diffraction Analysis, Fourier Transform Infrared Spectroscopy, surface area and pore volume.